Integracja rynku kapitałowego w Unii Europejskiej - rola operatorów w rozwoju polskiego rynku kapitałowego - Banaszczak-Soroka, Urszula (European Union Capital Market Integration - the Role of Operators at the Development of Polish Capital Market, 2008)
The creation of integrated financial market of the EU member states has been lasting for years already. "Initial report on the regulation of European Security Markets" enhanced the regulatory processes at the EU level and the obligation of their implementation in every member state. The objective of capital markets integration is the creation of stable and strong market which will enable the issuers to gain the capital for development and the investors to diversify the directions of investing savings. It's objective is also intensification of competitiveness of European market towards global market. For three years Poland is full member of the EU, it is worth then to try to evaluate the development of the Polish capital market which is included in the integration processes and which is looking for it's own place in the new reality. (original abstract)
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2008; Nr 19, s. 91-100